War Without Winners : Afghanistan's Uncertain Transition After the Cold War - Rais, Rasul Bakhsh (Karachi Oxford University Press, 1994)
The situation created by Soviet intervention in Afghanistan attracted scholarly attention worldwide. But though much was written on Afghanistan, little effort was made to understand the domestic roots of the confrontation, nor was any effort made to explain the linkage between internal strife and external invasion. In this first work of its kind Dr Rasul Bakhsh Rais analyses all the factors that led to the Afghan tragedy. He examines the nature of the Afghan state and society, the dynamics of the regional and global power structure, the externalization of the civil strife and the resultant fragmentation of political power, thereby adding a fresh perspective to the debate on the politics and security of Afghanistan.
Include Bibliography and Index
Keywords: Afghanistan -- Soviet Occupation of Afghanistan (1979-1989)